A New Non Quadratic Model For Unconstrained Non Linear Optimization - Basim Hassan; Nidhal Al-Assady (Al-Rafidain Journal of Computer Sciences and Mathematics)
A new non-quadratic model is proposed for solving unconstrained optimization problems, which modifies and develops the classical conjugate gradient methods. The technique has the same properties as the classical conjugate gradient method that can be applied to a quadratic function. An algorithm is derived and evaluated numerically for some standard test functions .The results indicate that, in general, the new algorithm is an improvement on the previous methods so it remains to be investigated.